La relación entre el acceso al crédito y la formalización de microempresas en la región Loreto durante el periodo 2015 – 2024 - Lopez Sias, Andrea Samantha (2025)
This research analyzes the relationship between access to credit and the formalization of microenterprises in the Loreto region during the period 2015 2024, in a context characterized by high levels of informality and low financial inclusion. Using a quantitative, correlational approach with a non-experimental longitudinal design, official time series data were employed to evaluate how key financial and business indicators evolved over the past decade. The main findings reveal a positive and statistically significant correlation between the volume of credit granted by commercial banks and the number of microenterprises formally registered, as well as between deposit mobilization and the percentage of businesses holding operating licenses. Furthermore, an inverse relationship was observed between credit delinquency rates and the level of formalization, suggesting that formalized microenterprises tend to demonstrate better repayment behavior. However, the study also notes that the continued reduction in physical financial infrastructure may be limiting the reach of these positive dynamics. The results lead to the conclusion that access to credit is a relevant factor in promoting formalization, though not sufficient on its own. A broader strategy addressing structural, regulatory, and geographic barriers is required to effectively foster enterprise formalization in the region.